Serve the people ang kasaysayan ng radikal na kilusan sa Unibersidad ng Pilipinas - Lumbera, Bienvenido L. 1932-. (Quezon City Ibon Books, 2008)
Collection of stories on activism and radical movements within the premier state university in the Philippines.
In Tagalog and some articles in English.
Keywords: Student movements -- Philippines; Radicalism -- Philippines -- History; Students -- Philippines -- Political activity